2014
DOI: 10.1002/2014gc005234
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the western Caribbean: Collision of the Cocos Ridge and upper plate deformation

Abstract: Subduction of the Cocos plate and collision of the Cocos Ridge have profound effects on the kinematics of the western Caribbean, including crustal shortening, segmentation of the overriding plate, and tectonic escape of the Central American fore arc (CAFA). Tectonic models of the Panama Region (PR) have ranged from a rigid block to a deforming plate boundary zone. Recent expansion of GPS networks in Panama, Costa Rica, and Colombia makes it possible to constrain the kinematics of the PR. We present an improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 72 publications
10
92
0
7
Order By: Relevance
“…The principal stress directions may also be affected by other factors. The subducting Cocos Ridge has been proposed to act as an indenter, as shown by a margin‐parallel component of fore‐arc deformation measured on Costa Rica GPS land stations [ LaFemina et al ., ; Kobayashi et al ., ]. With the exception of the deepest interval in Site U1379, the S Hmax directions we observe are approximately parallel and perpendicular to the isobaths of the Cocos Ridge flank and to the most westerly azimuths of the GPS velocities in the land area NW of the Osa peninsula (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal stress directions may also be affected by other factors. The subducting Cocos Ridge has been proposed to act as an indenter, as shown by a margin‐parallel component of fore‐arc deformation measured on Costa Rica GPS land stations [ LaFemina et al ., ; Kobayashi et al ., ]. With the exception of the deepest interval in Site U1379, the S Hmax directions we observe are approximately parallel and perpendicular to the isobaths of the Cocos Ridge flank and to the most westerly azimuths of the GPS velocities in the land area NW of the Osa peninsula (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The subduction of the Cocos Ridge produces basal erosion seaward of the Osa peninsula [ Vannucchi et al ., ]. The Cocos Ridge also acts as an indenter, as shown by the fanning pattern of deformation away from the Cocos Ridge axis measured by GPS [ LaFemina et al ., ; Kobayashi et al ., ]. The Osa peninsula lies on top of the subducted Cocos Ridge axis and its geology suggests that the bulk of the overriding plate there is a Cenozoic mélange resulting from the accretion of oceanic seamounts [ Vannucchi et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…LaFemina et al (2009 suggested that the collision of the Cocos Ridge contributes to the northwestward motion of the forearc sliver. The buoyant, thickened crust of the Cocos Ridge acts as an indenter (Gardner et al, 2013) and arc-parallel forearc motion, as well as relative (north)eastward motion of the Panama-Chocó block represents tectonic escape (Kobayashi et al, 2014). Phipps Morgan et al (2008) noticed that the Motagua fault zone at present does not crosscut the Central American forearc and does not continue towards the Central American trench.…”
Section: Central Americamentioning
confidence: 99%
“…In southern Costa Rica, the Cocos plate subducts northeastward beneath the Caribbean plate (locally the Panama Microplate) at the Middle American Trench at a rate of ∼80–90 mm/year (Figure ; Argus et al, ; DeMets, ; Kobayashi et al, ). The southeasternmost portion of the Cocos plate was created by the Cocos‐Nazca spreading center (Figure ) and contains many roughness elements and bathymetric features related to overprinting by the Galápagos Hot Spot (Figure ; Barckhausen et al, ; Hoernle et al, ; Lonsdale & Klitgord, ).…”
Section: Tectonic Framework and Subducting Bathymetrymentioning
confidence: 99%